Pendekatan HOT-Fit dalam Evaluasi Sistem Informasi Manajemen Penyelesaian Laporan (SIMPeL) pada Lembaga Ombudsman Republik Indonesia - Andriyani, Meilianti; Umniati, Naeli (LPPM, 2020)
SIMPeL is a system owned by ORI to facilitate the process of completing reports and improving public services. The increasing number of incoming public service maladministration reports is a challenge for ORI, especially how to monitor the number of incoming reports quickly and make the handling of reporting (complaints) integrated. This research uses the HOT-FIT analysis method to determine influence of Human components, Organization, and Technology influences on the utilization (Net Benefit) of SIMPeL in ORI office. The number of respondents in this study was 79 respondents SIMPeL users who are staff or assistants at representative offices and ORI headquarters. The data in this study were analyzed with the help of the SmartPLS program. The results of the study show that simultaneously humans, organizations, and technology are components that affect the utilization (Net Benefit) of SIMPeL in ORI. The effect of human, organizational, and technological components on SIMPeL utilization was 37.8% while the remaining 62.2% variance in SIMPeL utilization was influenced by other factors outside the three components. Partially, human and technology can also affect the utilization (Net Benefit) of SIMPeL in ORI, while organizational components are not an influential factor in the utilization of SIMPeL in ORI.